Efektivitas Pembelajaran Project Based Learning (PJBL) Berbantuan App Kahoot terhadap Kemampuan Matematis Siswa SMP - Ayudyaningtyas, Wulan; Purwosetiyono, FX Didik; Zuhri, M Saifuddin (Universitas PGRI Semarang, 2025)
This research aims to evaluate the effectiveness of the Project Based Learning (PjBL) model supported by the Kahoot application in improving the mathematical abilities of junior high school students. The research method used is Quasi-Experimental with a Posttest Only Control Design. The study population consists of eighth-grade students at SMP N 1 Lasem, divided into two classes as samples: the experimental class using Kahoot-assisted PjBL and the control class using conventional teaching methods. The sampling was done using cluster random sampling techniques. Data collection techniques include documentation, observation to monitor student engagement during the learning process, and essay-type post-tests to measure students' mathematical abilities. The results showed that the experimental class using Kahoot-assisted PjBL performed better than the students using conventional teaching methods. There is an effect of student engagement using Kahoot-assisted PjBL. The mathematical abilities of students using the Project Based Learning (PjBL) model assisted by the Kahoot app achieved mastery. Implementing the PjBL model supported by the Kahoot application can enhance students' mathematical ability skills in mathematics learning.